KNOWLEDGE OF DENGUE HEMORRHAGIC FEVER AND ITS INFLUENCE ON 5M-PLUS PRACTICES AMONG HOUSEWIVES - Ashari, Meta Ria; AF, Swaidatul Masluhiya; Devi, Hilda Mazarina (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Dengue hemorrhagic fever (DHF) is caused by the dengue virus transmitted by the Aedes aegypti mosquito. In 2022, Indonesia reported 45,387 dengue cases, resulting in 432 deaths. The knowledge of housewives influences the prevalence of DHF; those with better knowledge tend to exhibit more effective prevention behaviors. This study assessed the relationship between DHF knowledge and 5M-Plus behavior among housewives in the Pakisaji Health Center area, Malang Regency. This study employed a cross-sectional analytic observational design and included 270 respondents, with a sample size of 124 obtained through convenience sampling. The research utilized a questionnaire and analyzed data using Spearman's test. Results indicated that 80.6% of respondents had good knowledge of dengue, while 33.9% demonstrated sufficient 5M-Plus behavior. Spearman's test revealed a significant relationship between dengue knowledge and 5M-Plus behavior among housewives (r = 0.188, p = 0.037). Those with strong knowledge more readily understand and implement 5M-Plus practices. Future research should explore the link between dengue knowledge and the motivation of housewives to eliminate dengue mosquito nests.